Numerical solution of fuzzy delay differential equations under generalized differentiability by Euler's method - Sangameswaran, Indra Kumar (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we interpret a fuzzy delay differential equations using the concept of generalized differentiability. Using the Generalized Characterization Theorem, we investigate the problem of finding a numerical approximation of solutions. The Euler approximation method is implemented and its error analysis is discussed. The applicability of the theoretical results is illustrated with some examples.